2013
DOI: 10.1371/journal.pone.0074008
|View full text |Cite
|
Sign up to set email alerts
|

An Improved Quantitative Approach for the Assessment of Mitochondrial Fragmentation in Chemoresistant Ovarian Cancer Cells

Abstract: Mitochondrial fission is a process that involves cleavage of mitochondria into smaller fragments and is regulated by the GTPase Dynamin-related protein 1 (Drp1). Higher levels of mitochondrial fission are associated with the induction of apoptosis in cancer cells. However, current methods to accurately quantify mitochondrial fission in order to compare therapeutics that target this process are often ambiguous or rely on subjective assessment. Mitochondria are also prone to aggregation, making accurate analysis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
34
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(37 citation statements)
references
References 23 publications
2
34
1
Order By: Relevance
“…Given the role of mitochondria in the apoptotic response to chemotherapeutics [32], we suspect that in the latter case apoptosis ensues because of the exaggerated mitophagy. Thus, to improve the chance to cure ovarian carcinomas, one should carefully consider whether to employ autophagy inhibitors or autophagy-enhancer drugs in the chemotherapy cocktail depending on the ratio of BECLIN 1 and BCL-2 expression and the actual level of autophagy in the cancer cells.…”
Section: Discussionmentioning
confidence: 99%
“…Given the role of mitochondria in the apoptotic response to chemotherapeutics [32], we suspect that in the latter case apoptosis ensues because of the exaggerated mitophagy. Thus, to improve the chance to cure ovarian carcinomas, one should carefully consider whether to employ autophagy inhibitors or autophagy-enhancer drugs in the chemotherapy cocktail depending on the ratio of BECLIN 1 and BCL-2 expression and the actual level of autophagy in the cancer cells.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have demonstrated that cisplatin treatment activates mitochondrial fission and induces apoptosis [18,19]. However, the underlying mechanism of this effect remains poorly understood.…”
Section: Fis1 Regulates Mitochondrial Fission and Cisplatin Sensitivimentioning
confidence: 99%
“…Piperlongumine also enhanced cisplatin-induced apoptosis via increased levels of Drp 1-dependent mitochondrial fission. 13,110,142,143 …”
Section: 73mentioning
confidence: 99%